The European Union Strategy in the field of Cyber-security - Moise, Adrian-Cristian (International Journal of Legal and Social Order, 2023)
Cyber-attacks and cybercrime are increasing in number and sophistication across Europe. The article presents and analyzes the European Union strategy for the period 2020-2025 in the field of cyber-security, as well as the most important legal instruments and bodies that have concerns in the field of cyber-security. The aim of the European Union's cyber-security strategy is to strengthen Europe's resilience to cyber threats and ensure that all citizens and businesses can fully benefit from reliable and trustworthy digital services and tools. The European Union strategy in the field of cyber-security contains concrete proposals for the implementation of regulatory, investment and policy instruments.